INVESTMENT CLIMATE AS A FACTOR OF SOCIAL AND ECONOMIC DEVELOPMENT IN REGIONS OF THE RUSSIAN FEDERATION - Gubanova, Maria Andreevna; Bessonova, Elena Anatolyevna; Anoshina, Iulia Fedorovna (Journal of Applied Engineering Science, 2017)
In this article, the authors attempt to view into the notions of investment potential, investment climate and investment activity, as well as to analyze investment attractiveness of modern Russia due to its place in different global ratings. We also analyze the operation of regions in the situation of sanction restrictions, the amount of direct foreign investments into different enterprises on the territory of the country. We evaluate investment potential of regions in Central Federal District for eight indicators and give recommendations for increasing investments to the regions, which is to provide a higher level of adaptability of development strategies in the dynamic and complex economic environment.